2021
DOI: 10.1002/adhm.202100131
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cell‐Derived Neural Progenitor Cells Produce Distinct Neural 3D In Vitro Models Depending on Alginate/Gellan Gum/Laminin Hydrogel Blend Properties

Abstract: Stable and predictive neural cell culture models are a necessary premise for many research fields. However, conventional 2D models lack 3D cell‐material/‐cell interactions and hence do not reflect the complexity of the in vivo situation properly. Here two alginate/gellan gum/laminin (ALG/GG/LAM) hydrogel blends are presented for the fabrication of human induced pluripotent stem cell (hiPSC)‐based 3D neural models. For hydrogel embedding, hiPSC‐derived neural progenitor cells (hiNPCs) are used either directly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Our data showed that it is possible to make RPE and RO co-grafts using alginate as a bio-adhesive. Previous investigations demonstrated that alginate can be used for tissue engineering and other biomedical applications ( Kuo and Ma, 2001 ; Espona-Noguera et al, 2018 ; Hontani et al, 2019 ; Yeo and Kim, 2020 ; Kapr et al, 2021 ). It’s application in wound healing, drug delivery, and tissue engineering is well established due its ability to retain structural similarity to the extracellular matrices in tissues ( Lee and Mooney, 2012 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that it is possible to make RPE and RO co-grafts using alginate as a bio-adhesive. Previous investigations demonstrated that alginate can be used for tissue engineering and other biomedical applications ( Kuo and Ma, 2001 ; Espona-Noguera et al, 2018 ; Hontani et al, 2019 ; Yeo and Kim, 2020 ; Kapr et al, 2021 ). It’s application in wound healing, drug delivery, and tissue engineering is well established due its ability to retain structural similarity to the extracellular matrices in tissues ( Lee and Mooney, 2012 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, only exopolysaccharides (except for bacterial cellulose that was considered in Section 2.2 ) will be reviewed since they are the most commonly used microbial polysaccharides for bioprinting applications [ 26 ]. The usage of these polysaccharides in 3D bioprinting is still gaining ground since the exploitation of microbial-derived polysaccharides-based bioinks has only been recently described in the literature [ 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ], as summarized in Table 3 .…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%
“…Moreover, the presence of carboxylic groups in its structure allows the formation of hydrogels in the presence of mono and divalent ions, such as Na + , K + and Mg 2+ , Ca 2+ , respectively [ 173 ]. Gellan gum hydrogels obtained by ionotropic crosslinking are brittle and mechanically weak, so it is normally necessary to chemically modify [ 157 ] or blend them with other polymers [ 153 , 158 , 159 , 160 , 161 , 162 ] to obtain printable bioinks.…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%
“…Scaffold materials are usually selected to fit the paradigms of a particular question of interest. The most used scaffold for 3D neural cell cultures is Matrigel, but others have opted for more specialized tissue-engineering materials, including alginate-gellan gum-laminin blends [ 93 ], microfibrous PLGA [ 94 ], designer self-assembled peptides [ 95 ], and decellularized porcine brain ECM [ 96 ], which has also been tested as an external scaffold for spheroids [ 97 ]. Likewise, an early adopter of 3D culture for AD modeling, Zhang et al [ 98 ], created iPSC-derived neuronal organoids in a 3D matrix made of RADA-16, a self-assembling amphiphilic peptide.…”
Section: Modeling Alzheimer’s Diseasementioning
confidence: 99%